Heterogeneity in interventions in village committee and farmland circulation: Intermediary versus regulatory effects. (May 2018) - Shi, Xiaoping; Chen, Shujie; Ma, Xianlei; Lan, Jing
Abstract: Through comparing the intermediary regulatory effects, this paper investigates the effects of the village committee on farmer households' participation in farmland circulation based on rural household survey data from Jiangsu and Jiangxi collected in 2014. Our results indicate that farmers' lack of trust in the village committee probably weakens the intermediary effect, and so reduces the possibility of households' participating in renting lands. In addition, farmland circulation information provided by the village committee can promote farmland circulation in terms of renting out lands, but it demonstrates a "discriminatory" effect on households' renting decisions as the significant effect can only be found for participants who are renting large-scale farmlands. Furthermore, the regulatory effect induced by the village committee tends to reduce households' participation in farmland circulation with respect to both renting and renting out the lands. Finally, the "heterogeneous" regulatory effect is inclined to distort the household's expectations of risk from participating in farmland circulation.